Clinical predictors of COVID‐19 severity and bleeding in the ACTIV‐4B COVID‐19 outpatient thrombosis prevention trial. Issue 7 (11th April 2022) - Connors, Jean M.; Brooks, Maria M.; Sciurba, Frank C.; Fu, Zhuxuan; Ridker, Paul M.
Abstract :